2009
DOI: 10.1590/s0102-695x2009000300016
|View full text |Cite
|
Sign up to set email alerts
|

Atividades antimicrobiana e leishmanicida das sementes de Pterodon emarginatus Vogel

Abstract: "Antimicrobial and leishmanicidal activities of seeds of Pterodon emarginatus". The present work investigated the antimicrobial and leishmanicidal activities of seeds of Pterodon emarginatus. The tests of diffusion in agar (10, 25 and 50 mg) and determination of minimum inhibitory concentration (MIC) were performed using essential oil (EO) obtained from seeds using the standard microorganisms: Staphylococcus aureus ATCC 25923, Streptococcus mutans ATCC 25175, Pseudomonas aeruginosa ATCC 90271, Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
2
14
0
4
Order By: Relevance
“…Similar results were described by Dutra et al .,[15] when evaluating the MIC of ethanolic of P. emarginatus using broth diffusion methods against S. aureus . The authors observed that, in the broth microdilution test, the extract presented antibacterial activity with MIC at 2.5 mg/mL.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were described by Dutra et al .,[15] when evaluating the MIC of ethanolic of P. emarginatus using broth diffusion methods against S. aureus . The authors observed that, in the broth microdilution test, the extract presented antibacterial activity with MIC at 2.5 mg/mL.…”
Section: Discussionsupporting
confidence: 86%
“…[15] In animals, S. aureus can contaminate and produce various abscesses and pyogenic infections such as endocarditis, septic arthritis and osteomyelitis, food poisoning syndrome, desquamation, and toxic shock syndrome. [1617] Microbial resistance to various drugs is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous reports indicate save treatment with P. pudescens extracts components without side effects observed (Dutra et al, 2009).…”
Section: Parasite Per Macrophage Cells Viability (%)mentioning
confidence: 95%
“…Several works suggest immuno modulatory and anti-protozoa effect of plant component of Pterodon genera without side effects observed (Cardoso et al, 2008;Menna-Barreto et al, 2008;Dutra et al, 2009;Coelho et al, 2004). Recently, anti-tumoral effects have been shown for Pterodon pubescens extracts using in vitro model of leukemia (Pereira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although P. emarginatus is considered to be an important source of phytotherapeutic material because of its phytochemical characteristics and bioactive properties (Machado et al., ), few studies have been conducted on the use of its essential oil (Alves et al., ; Dutra et al., ; Mors et al., ; Pascoa et al., ; Santos et al., ). Because of the characteristics and properties of P. emarginatus , this plant has been included in the list of species that are a conservation priority (Alves et al., ).…”
Section: Introductionmentioning
confidence: 99%